2017
DOI: 10.1152/japplphysiol.00104.2017
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of globin proteins in hypoxia-tolerant ectothermic vertebrates

Abstract: Globins are heme-containing proteins ubiquitously expressed in vertebrates, where they serve a broad range of biological functions, directly or indirectly related to the tight control of oxygen levels and its toxic products in vivo. Perhaps the most investigated of all proteins, hemoglobin and myoglobin are primarily involved in oxygen transport and storage, but also in facilitating arterial vasodilation, suppressing mitochondrial respiration, and preventing tissue oxidative damage via accessory redox enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…Deoxygenated globin proteins can reduce nitrite to NO . All PanMbs except PanMb6b display noticeable nitrite reductase activity (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deoxygenated globin proteins can reduce nitrite to NO . All PanMbs except PanMb6b display noticeable nitrite reductase activity (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…While reducing NO, oxy‐Mb is oxidised to met‐Mb that needs to be reduced by the cellular Mb reductase . Furthermore, under hypoxia, Mb has the opposite effect whereby deoxy‐Mb functions as nitrite reductase producing NO from nitrite (NO2-) , thereby limiting O 2 consumption rates . It has also been suggested that Mb functions in oxidative defence by removing reactive oxygen species (ROS) .…”
Section: Introductionmentioning
confidence: 99%
“…It should be borne in mind that the bar-headed goose is exposed to high altitude only during seasonal migrations, while spending long periods of the year at low to moderate altitudes (Bishop et al, 2015;Hawkes et al, 2013Hawkes et al, , 2011Scott et al, 2015). Changes in RBC levels of organic phosphates result in immediate and reversible adjustments in blood O 2 transport properties to altitude variations, as found in species in which the levels of organic phosphates change during hypoxia (Fago, 2017;Weber, 2007;Weber and Fago, 2004). Whether IPP levels of RBCs change significantly upon altitude exposure in the bar-headed goose remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…of productive scientific collaborations fostered in this congenial, cross-disciplinary environment, keynote speakers have produced 18 mini-reviews that appear in successive issues this fall. The Journal has also accepted other research papers (2, 3, 6, 9, 12, 13, 16, 20-22, 25, 29) and related mini reviews (10,14) for this Highlighted Topic in Hypoxia. Readers will enjoy the diverse topics reflecting the broad impact and translation of hypoxia on many areas of physiology and medicine.…”
mentioning
confidence: 91%